Evaluation of Cardiovascular Biomarkers and Lipid Profiles in Diabetic Patients Undergoing Coronary Artery Bypass Grafting (CABG) Surgery Compared to a Control Group - Golbashirzadeh, morteza; moradzadegan, Hosein; Moradzadegan , Atousa (Biomedical Sciences and Clinical Medicine, 2026)
Objective Cardiovascular diseases (CVDs), particularly coronary artery disease (CAD), remain among the leading causes of morbidity and mortality worldwide. Type 2 diabetes mellitus (T2DM) significantly accelerates the progression of CAD through metabolic disturbances, including dyslipidemia and elevated homocysteine levels. This study aimed to evaluate cardiovascular biomarkers and lipid profiles in diabetic patients undergoing coronary artery bypass grafting (CABG) surgery, compared to a non-diabetic control group. Methods A total of 200 participants were included in this study, consisting of 100 patients with type 2 diabetes who had undergone CABG or angioplasty, and 100 age‑matched individuals with type 2 diabetes without any history of cardiovascular disease, who served as controls. Results Homocysteine levels were elevated in 75.0% of diabetic patients versus 58.0% of controls (p = 0.03). Low high-density lipoprotein cholesterol (HDL-C) was observed in 93.0% of diabetics compared to 68.0% of controls (p = 0.01). No statistically significant differences were found in total cholesterol, low-density lipoprotein cholesterol (LDL-C), troponin, or CK-Mb levels between groups (p > 0.05). These findings suggest that hyperhomocysteinemia and low HDL-C are significantly associated with CAD in diabetic populations. The presence of elevated homocysteine in a substantial proportion of the control group may reflect subclinical metabolic dysfunction or undiagnosed risk factors, warranting further investigation. Conclusions These results underscore the potential utility of homocysteine and HDL-C as biomarkers in cardiovascular risk stratification. Their integration into routine screening protocols may enhance early detection and preventive strategies, particularly in high-risk or resource- limited settings.